2021
DOI: 10.3390/ijms22041717
|View full text |Cite
|
Sign up to set email alerts
|

Packaging Covered with Antiviral and Antibacterial Coatings Based on ZnO Nanoparticles Supplemented with Geraniol and Carvacrol

Abstract: The purpose of the study was to obtain an external coating based on nanoparticles of ZnO, carvacrol, and geraniol that could be active against viruses such as SARS-Co-V2. Additionally, the synergistic effect of the chosen substances in coatings was analyzed. The goal of the study was to measure the possible antibacterial activity of the coatings obtained. Testing antiviral activity with human pathogen viruses, such as SARS-Co-V2, requires immense safety measures. Bacteriophages such as phi 6 phage represent go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(81 citation statements)
references
References 25 publications
(44 reference statements)
1
61
0
Order By: Relevance
“…The study demonstrated that boxes containing polyethylene films (PE) coated with an active layer consisting of methylhydroxy-propyl-cellulose (MHPC) with nanoparticles of zinc oxide were found to be very active films to extend the shelf life of cod fillets. Another good example is a previous study by the author [4] which demonstrated that a PE covered with MHPC coating/layers with a very small amount of nanoparticles of zinc oxide, as well as geraniol or carvacrol, were found to be very good, active films to extend the shelf life of food products. Additionally, a synergistic effect between active additives/compounds mentioned above was also noticed.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The study demonstrated that boxes containing polyethylene films (PE) coated with an active layer consisting of methylhydroxy-propyl-cellulose (MHPC) with nanoparticles of zinc oxide were found to be very active films to extend the shelf life of cod fillets. Another good example is a previous study by the author [4] which demonstrated that a PE covered with MHPC coating/layers with a very small amount of nanoparticles of zinc oxide, as well as geraniol or carvacrol, were found to be very good, active films to extend the shelf life of food products. Additionally, a synergistic effect between active additives/compounds mentioned above was also noticed.…”
Section: Introductionmentioning
confidence: 97%
“…Active substances which are responsible for the antimicrobial activity of the packaging can be introduced into the polymer matrix or the coating. The active coatings are typically manufactured using biopolymers derived from various natural plant and animal sources, such as polysaccharides with the addition of other active substances [2][3][4]. An excellent example of the use of active packaging to extend the shelf-life of food products was offered by a previous work carried out by the author [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among many nanomaterials, zinc oxide nanostructures are exceptionally attractive thanks to their unique functional properties and the diversity of their applications. They have been used in many fields as gas sensors [ 8 ], piezoelectric devices [ 9 ], solar cells [ 10 ], fillers in polymeric nanocomposites [ 11 , 12 ], coatings [ 13 , 14 ], antimicrobial agents [ 15 ], and in textiles [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various nanomaterials have been investigated for antiviral and antibacterial effects. Mizielińska et al reported the potential antibacterial activity of the coatings based on nanoparticles of ZnO, carvacrol, and geraniol [ 12 ]. Kong et al reported a unique toxicity based on Co-NPs based on their sizes.…”
mentioning
confidence: 99%